(untitled) (Revista "Boletín el Conuco", 2020)
This research presents the analyzes that were carried out after the development of the Academic Exchange Day between the “Universidad de los Llanos” and the “Universidad Veracruzana de México”. This was an activity developed under the substantive mission of Social Projection. This is a qualitative study that involved four students from Coatzatoalcos - Mexico and four students from Villavicencio - Colombia, who participated in university internationalization processes in the last year. Some important aspects associated with the positioning of the “Universidad de los Llanos” were analyzed, in order to identify the elements that influence their choice whe